FEATURES OF THE ADMINISTRATIVE AND LEGAL STATUS OF THE MAYOR OF KYIV - Sheihas, Maryna (Global Prosperity, 2022)
The article is devoted to determining the features of the administrative and legal status of the mayor of Kyiv. The author disclosed the essence of the nature of the powers of the mayor of Kyiv. The author also analyzed the legal consolidation of his powers. The purpose of the article is to determine the features of the administrative and legal status of the Kyiv mayor as the senior official of the territorial community of the city of Kyiv. Certain features of the administrative and legal status of the Kyiv mayor are related to the performance of the city of Kyiv’s capital functions. The nature and essence of the combination of the Kyiv mayor’s positions and the Head of the Kyiv City State Administration have been studied. The main shortcomings of the current state of legislative support for the Kyiv mayor’s status are revealed. The author concluded that we propose to differentiate the legal regulation of the status of Kyiv mayor on three levels: basic - which includes the provisions of the Constitution of Ukraine and defines the main feature, which is special legislative enshrinement of local government in Kyiv; legislative - formed by the Laws of Ukraine "On Local Self-Government in Ukraine", "On Local State Administrations", "On the Capital of Ukraine - the Hero City of Kyiv". The set of provisions of these legislative acts reveals the main scope and scope of powers of the Kyiv mayor, the peculiarity of his combination of local government functions, government officials, as well as political functions related to the special status of Kyiv as the capital of Ukraine; local - embodied in the decision of the Kyiv City Council, which approved the Charter of the territorial community of Kyiv.